Urinary C‐peptide creatinine ratio detects absolute insulin deficiency in Type 2 diabetes - Hope, S. V. (Blackwell Science, 2013)
AIMS: To determine the prevalence and clinical characteristics of absolute insulin deficiency in long‐standing Type 2 diabetes, using a strategy based on home urinary C‐peptide creatinine ratio measurement. METHODS: We assessed the urinary C‐peptide creatinine ratios, from urine samples taken at home 2 h after the largest meal of the day, in 191 insulin‐treated subjects with Type 2 diabetes (diagnosis age ≥45 years, no insulin in the first year). If the initial urinary C‐peptide creatinine ratio was ≤0.2 nmol/mmol (representing absolute insulin deficiency), the assessment was repeated. A standardized mixed‐meal tolerance test with 90‐min stimulated serum C‐peptide measurement was performed in nine subjects with a urinary C‐peptide creatinine ratio ≤ 0.2 nmol/mmol (and in nine controls with a urinary C‐peptide creatinine ratio >0.2 nmol/mmol) to confirm absolute insulin deficiency. RESULTS: A total of 2.7% of participants had absolute insulin deficiency confirmed by a mixed‐meal tolerance test. They were identified initially using urinary C‐peptide creatinine ratio: 11/191 subjects (5.8%) had two consistent urinary C‐peptide creatinine ratios ≤ 0.2 nmol/mmol; 9 of these 11 subjects completed a mixed‐meal tolerance test and had a median stimulated serum C‐peptide of 0.18 nmol/l. Five of these 9 had stimulated serum C‐peptide <0.2 nmol/l and 9/9 subjects with urinary C‐peptide creatinine ratio >0.2 had endogenous insulin secretion confirmed by the mixed‐meal tolerance test. Compared with subjects with a urinary C‐peptide creatinine ratio >0.2 nmol/mmol, those with confirmed absolute insulin deficiency had a shorter time to insulin treatment (median 2.5 vs. 6 years, P=0.005) and lower BMI (25.1 vs. 29.1 kg/m(2), P=0.04). Two out of the five patients with absolute insulin deficiency were glutamic acid decarboxylase autoantibody‐positive. CONCLUSIONS: Absolute insulin deficiency may occur in long‐standing Type 2 diabetes, and cannot be reliably predicted by clinical features or autoantibodies. Absolute insulin deficiency in Type 2 diabetes may increase the risk of hypoglycaemia and ketoacidosis, as in Type 1 diabetes. Its recognition should help guide treatment, education and management. The urinary C‐peptide creatinine ratio is a practical non‐invasive method to aid detection of absolute insulin deficiency, with a urinary C‐peptide creatinine ratio > 0.2 nmol/mmol being a reliable indicator of retained endogenous insulin secretion.